Is artists' perception more veridical? - Perdreau, Florian (Frontiers Media S.A., 2013)
Figurative artists spend years practicing their skills, analyzing objects, and scenes in order to reproduce them accurately. In their drawings, they must depict distant objects as smaller and shadowed surfaces as darker, just as they are at the level of the retinal image. However, this retinal representation is not what we consciously see. Instead, the visual system corrects for distance, changes in ambient illumination and view-point so that our conscious percept of the world remains stable. Does extensive experience modify an artist's visual system so that he or she can access this retinal, veridical image better than a non-artist? We have conducted three experiments testing artists' perceptual abilities and comparing them to those of non-artists. The subjects first attempted to match the size or the luminance of a test stimulus to a standard that could be presented either on a perspective grid (size) or within a cast shadow. They were explicitly instructed to ignore these surrounding contexts and to judge the stimulus as if it were seen in isolation. Finally, in a third task, the subjects searched for an L-shape that either contacted or did not contact an adjacent circle. When in contact, the L-shape appeared as an occluded square behind a circle. This high-level completion camouflaged the L-shape unless subjects could access the raw image. However, in all these tasks, artists were as much affected by visual context as novices. We concluded that artists have no special abilities to access early, non-corrected visual representations and that better accuracy in artists' drawings cannot be attributed to the effects of expertise on early visual processes.